2017
DOI: 10.3389/fphys.2017.00663
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Oral Sensory Effects of Three TRPA1 Agonists in Young Adult Smokers and Non-smokers

Abstract: This study profiled intra-oral somatosensory and vasomotor responses to three different transient receptor potential (TRP) channels, subfamily A, member 1 (TRPA1) agonists (menthol, nicotine, and cinnamaldehyde) in smoking and non-smoking young adults. Healthy non-smokers (N = 30) and otherwise healthy smokers (N = 25) participated in a randomized, double-blinded, cross-over study consisting of three experimental sessions in which they received menthol (30 mg), nicotine (4 mg), or cinnamaldehyde (25 mg) chewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…When applied topically on the skin, cinnamaldehyde produces spontaneous pain, heat and mechanical hyperalgesia, cold hypoalgesia, neurogenic axon reflex erythema, intensified warm sensations, reduced heat pain threshold, moderate itch, flare, hyperkinesis, allokinesis, and increased skin blood flow and temperature (30,53,135,322,575,630,740). In the human tongue, cinnamaldehyde enhances both heat-and cold-induced pain (14,685), increases the local temperature (353), and produces burning sensation (301). When applied to human airways, this compound produces smart (stinging pain) ( 16), cough (365), and weak burning sensation (134).…”
Section: Activation By Natural Compoundsmentioning
confidence: 99%
“…When applied topically on the skin, cinnamaldehyde produces spontaneous pain, heat and mechanical hyperalgesia, cold hypoalgesia, neurogenic axon reflex erythema, intensified warm sensations, reduced heat pain threshold, moderate itch, flare, hyperkinesis, allokinesis, and increased skin blood flow and temperature (30,53,135,322,575,630,740). In the human tongue, cinnamaldehyde enhances both heat-and cold-induced pain (14,685), increases the local temperature (353), and produces burning sensation (301). When applied to human airways, this compound produces smart (stinging pain) ( 16), cough (365), and weak burning sensation (134).…”
Section: Activation By Natural Compoundsmentioning
confidence: 99%
“…This preliminary study reported subjects sensitized to the aldehyde reporting more burning complaints when exposed to nicotine. Both cinnamaldehyde and nicotine also alter the vasomotor activity in the oral and pharyngeal mucosa, and chronic exposure may modify pain reception in these areas 118 . To our knowledge, no publication has addressed this effect in e-cig users.…”
Section: Mucosal Painmentioning
confidence: 99%
“…TRPA1 channel has been identified in many cell types in the airways, principally in airway sensory neurons (spinal dorsal root ganglia, nasal trigeminal, and vagal neurons), but also in lung fibroblasts, airway smooth muscle cells, bronchial and alveolar epithelium cells. 11,20 TRPA1 channel is considered an important part of the lungs defense system and immunohistochemical studies have identified TRPA1 also in oropharynx and larynx. 21 The vagal and trigeminal ganglia innervating airways show appreciable TRPA1 expression.…”
Section: Discussionmentioning
confidence: 99%